Family-centered care in pediatric critical care units: A critical review - Patricia Rubio-Garrido; Leticia Bazo-Hernández; Anna Enrich-Font; Ana María Montserrat-Gala; Cristina Pavón-García; María-Concepción Lasmarías-Ugarte; María-Antonia Martorell-Poveda; María Francisca Jiménez-Herrera (Journal of Pediatric Critical Care)
Family-centered care (FCC) in pediatric intensive care units (PICUs) arises as a response to the need to humanize medical care, integrating families as active allies in the care of the hospitalized child. This approach seeks to improve the quality of care, the emotional well-being of caregivers, patient adaptation, and prioritizing principles such as respect, communication, participation, and mutual support. This review article highlights the positive impact of FCC on the reduction of stress, anxiety, and hospital stay, as well as on the satisfaction of family members. Strategies such as humanization of the environment through play activities, psychological support, and preparation for transition after PICUs are essential. However, their application is still uneven and faces institutional, organizational, and training barriers. Systematic implementation of the model requires the commitment of the healthcare team, continuous training, and tools to evaluate its real impact. The active involvement of families not only favors the recovery of the child but also improves the perception of the care received, becoming a key indicator of quality in pediatric intensive care.